Medicine meets virtual reality : art, science, technology : healthcare (r)evolution : proceedings - Westwood, James D. ed....[et al] (IOS Press AmsterdamNL, 1998)
Looks at aspects such as telemedicine, robotics, simulation and other new technologies.